Sequence variability in p6 gag protein and gag/pol coevolution in Human Immunodeficiency Type 1 Subtype F genomes - Rossi, Andrés Hugo (2013)
Polymorphisms occurring at the p6gag protein of HIV-1 have been previously found to have an impact on viral fitness and antiretroviral (ARV) resistance, mainly on subtype B genomes. We compared p6gag variability in a large group of 165 subtype F gag-pol sequences, with 36 subtype B sequences from the same study source, and identified sites of gag-pol coevolution under ARV selection pressure. Subtype-specific differences in the frequency of point mutations, insertions, and deletions previously associated with ARV resistance were found. Also, in our dataset of subtype F genomes a strong association between mutation P5L in the p1/p6 cleavage region of gag and the nelfinavir (NFV) resistance mutation N88DPR was found with no impact on the preference for any of the NFV resistance pathways.